Individual, social, and family factors associated with high school dropout among low‐SES youth: Differential effects as a function of immigrant status. (28th April 2017) - Archambault, Isabelle; Janosz, Michel; Dupéré, Véronique; Brault, Marie‐Christine; Andrew, Marie Mc
Abstract : Background: In most Western countries, the individual, social, and family characteristics associated with students' dropout in the general population are well documented. Yet, there is a lack of large‐scale studies to establish whether these characteristics have the same influence for students with an immigrant background. Aims: The first aim of this study was to assess the differences between first‐, second‐, and third‐generation‐plus students in terms of the individual, social, and family factors associated with school dropout. Next, we examined the differential associations between these individual, social, and family factors and high school dropout as a function of students' immigration status. Sample: Participants were 2291 students (54.7% with an immigrant background) from ten low‐SES schools in Montreal (Quebec, Canada). Method: Individual, social, and family predictors were self‐reported by students in secondary one (mean age = 12.34 years), while school dropout status was obtained five or 6 years after students were expected to graduate. Results: Results of logistic regressions with multiple group latent class models showed that first‐ and second‐generation students faced more economic adversity than third‐generation‐plus students and that they differed from each other and with their native peers in terms of individual, social, and family risk factors. Moreover, 40% of the risk factors considered in this study were differentially associated with first‐, second‐, and third‐generation‐plus students' failure to graduate from high school. Conclusion: These results provide insights on immigrant and non‐immigrant inner cities' students experiences related to school dropout. The implications of these findings are discussed.